Financial institutions, markets and money - Kidwell, David S.; Blackwell, David W.; Whidbee, David A.; Sias, Richard W. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Financial Institutions, Markets, and Money presents a balanced introduction to the operation, mechanics, and structure of the U.S. financial system. This eleventh edition expands coverage of Federal Reserve System and its conduct of monetary policy.
Includes index.
rua 29/01/14
Loans
Keywords: Finance; Financial institutions; Banks and banking; Monetary policy